Building Digital Archives for Scientific Information - Leah Solla (Issues in Science and Technology Librarianship, 2002)
The article discusses several digitial archives for scientific literature, including Project PRISM, the Electronic Mathematics Archives Initiative (EMANI), Project Euclid, the Digital Mathematics Library (DML), and arXiv.